Anti-cancer Effects of 1,4-Dialkoxynaphthalene-Imidazolium Salt Derivatives through ERK5 kinase activity inhibition - Haena Lee; Anh-Thu Nguyen; Hyunkyung Choi; Ki-Young Kim; Hakwon Kim (Scientific Reports)
Abstract ERK5 has emerged as a promising therapeutic target in cancer treatment due to its pivotal role in regulating tumor cell proliferation and survival. In this study, we synthesized novel derivatives of 1,4-dialkoxynaphthalene-2-acyl or 2-alkyl-imidazolium salt (NAIMS), assessed their binding affinity with the ERK5 protein through molecular modeling, and evaluated their anti-cancer activity through the ERK5 kinase assay. Based on the MTT assay and qRT-PCR analysis of 21 synthesized NAIMS, the IC50 values for 4c, 4e, and 4k (8.5 μM, 6.8 μM, and 8.9 μM, respectively) and the inhibition rate of the expression of PCNA for 4c, 4e, and 4k (50%, 61.1%, and 70.2% of 5 μM respectively) were chosen for comprehensive biological research. Further analyses including DAPI staining, and flow cytometry confirmed that 4c, 4e, and 4k induced late-stage apoptosis, and triggered cell cycle arrest in the G2/M phase of HeLa cells. Moreover, molecular modeling analysis showed that 4e exhibited strong and stable molecular interactions at the ERK5 ATP-binding site. Our results strongly suggest that NAIMS compounds, especially 4e, could serve as novel inhibitors of ERK5, presenting promising lead compound to develop for cancer treatment.